Implementation of a trauma registry in a brazilian public hospital: the first 1,000 patients - Carreiro,Paulo Roberto Lima (2014)
OBJECTIVE: Show the steps of a Trauma Registry (TR) implementation in a Brazilian public hospital and evaluate the initial data from the database.METHODS: Descriptive study of the a TR implementation in João XXIII Hospital (Hospital Foundation of the state of Minas Gerais) and analysis of the initial results of the first 1,000 patients.RESULTS: The project was initiated in 2011 and from January 2013 we began collecting data for the TR. In January 2014 the registration of the first 1000 patients was completed. The greatest difficulties in the TR implementation were obtaining funds to finance the project and the lack of information within the medical records. The variables with the lowest completion percentage on the physiological conditions were: pulse, blood pressure, respiratory rate and Glasgow coma scale. Consequently, the Revised Trauma Score (RTS) could be calculated in only 31% of cases and the TRISS methodology applied to 30.3% of patients. The main epidemiological characteristics showed a predominance of young male victims (84.7%) and the importance of aggression as a cause of injuries in our environment (47.5%), surpassing traffic accidents. The average length of stay was 6 days, and mortality 13.7%.CONCLUSION: Trauma registries are invaluable tools in improving the care of trauma victims. It is necessary to improve the quality of data recorded in medical records. The involvement of public authorities is critical for the successful implementation and maintenance of trauma registries in Brazilian hospitals.